Transformasi Nitrogen secara Biologis di Air Panas Sarongsong Kota Tomohon - Frity Lisa Taroreh; Ferry Karwur; Jubhar Mangimbulude (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Nitrogen transformation is the alteration process of nitrogen compounds from one form to another occurred in the nature. The transformation can even occur in an extreme environment, such a hot springs, and get through processes, including amonification, nitrification and denitrification. The research objective was to determine the hydrochemicals/ characteristics of water physically and chemically, as well as to determine whether nitrogen transformation occured through the processes of amonification, nitrogen, nitrification and denitrification in Sarongsong hot spring. Samples in the research were taken from Sarongsong Hot spring, Tomohon City at three different stations and were grouped in two: aerobic and anaerobic. This research was undertaken in CARC laboratory, master’s program of biology, SWCU, Salatiga. The level of ammonium, nitrite and nitrate at three stations (S1, S2, S3) at early period of the research were measured. Levels of ammonium, nitrite, and nitrate at S1 respectively are: 4.85mg/ L; 0.00mg/ L; 0.00mg/ L; at S2: 2.45mg/ L; 0.00mg/ L; 0.00mg/ L; on S3: 4.37mg/ L; 0.00mg/ L; 0.00mg / L. following 7 days of treatment, levels of ammonium, nitrite and nitrate in S1, S2, S3 at the condition of the aerobic and anaerobic has altered in concentration, that  is an indication of nitrogen transformation process (amonification process) in Sarongsong hot spring, Tomohon City.